Application of Microextraction Techniques Including SPME and MESI to the Thermal Degradation of Polymers: A Review. (4th March 2017) - Kaykhaii, Massoud; Linford, Matthew R.
ABSTRACT: Here, we discuss the newly developed micro and solventless sample preparation techniques SPME (Solid Phase Microextraction) and MESI (Membrane Extraction with a Sorbent Interface) as applied to the qualitative and quantitative analysis of thermal oxidative degradation products of polymers and their stabilizers. The coupling of these systems to analytical instruments is also described. Our comprehensive literature search revealed that there is no previously published review article on this topic. It is shown that these extraction techniques are valuable sample preparation tools for identifying complex series of degradation products in polymers. In general, the number of products identified by traditional headspace (HS-GC-MS) is much lower than with SPME-GC-MS. MESI is particularly well suited for the detection of non-polar compounds, therefore number of products identified by this technique is not also to the same degree of SPME. Its main advantage, however, is its ability of (semi-) continuous monitoring, but it is more expensive and not yet commercialized.